2018
DOI: 10.1111/apha.13105
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous pH landscape as a facilitator of melanoma initiation and progression

Abstract: Melanoma incidence is on the rise and currently causes the majority of skin cancer-related deaths. Yet, therapies for metastatic melanoma are still insufficient so that new concepts are essential. Malignant transformation of melanocytes and melanoma progression are intimately linked to the cutaneous pH landscape and its dysregulation in tumour lesions. The pH landscape of normal skin is characterized by a large pH gradient of up to 3 pH units between surface and dermis. The Na /H exchanger NHE1 is one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 188 publications
(230 reference statements)
1
6
0
1
Order By: Relevance
“…For FTIR and TRIR measurements, DOPA melanin powder was dissolved at 5 mg mL −1 in phosphate-buffered D 2 O solution, containing 25 m m each of sodium phosphate monobasic and sodium phosphate dibasic. The pD value of the buffer and DOPA melanin solution was 7.6 ± 0.1, which is close to what is expected in the stratum spinosum and stratum basale in human skin, where melanocytes produce melanins 51 .…”
Section: Methodssupporting
confidence: 82%
“…For FTIR and TRIR measurements, DOPA melanin powder was dissolved at 5 mg mL −1 in phosphate-buffered D 2 O solution, containing 25 m m each of sodium phosphate monobasic and sodium phosphate dibasic. The pD value of the buffer and DOPA melanin solution was 7.6 ± 0.1, which is close to what is expected in the stratum spinosum and stratum basale in human skin, where melanocytes produce melanins 51 .…”
Section: Methodssupporting
confidence: 82%
“…6 S-nitrosothiols concentration in human skin after irradiation at 320 nm (UVA) in comparison with the control (dark). The skin samples were pre-incubated with a solution of NaNO 3 at different concentrations (50, 500, 1000 and 5000 μmol L −1 ) for 1 h at 25 °C in the dark with the absorption spectra of urocanic acid and melanin, respectively (Gibbsl et al 1993;Geng et al 2008;Zonios et al 2008;Koch and Schwab, 2018;Madkhali et al 2019). Gibbsl et al 1993 showed that urocanic acid has an isomerization reaction at 310-320 nm (Gibbsl et al 1993) and Geng et al 2008 showed that melanin has a protective role against UVC-induced DNA damage (Geng et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что SLC9A1 -мембранный белок, переносящий Na + в клетку и H + из клетки -играет центральную роль в регуляции гомеостаза pH и является одним из основных источников кислотности в поверхностных слоях кожи [8]. Он также активируется наиболее частой мутацией при меланоме, BRAFV600E, тем самым вызывая нарушение регуляции pH во время инициации меланомы.…”
Section: сокращенияunclassified